2022
DOI: 10.1016/j.tige.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid APC Colon EMR, A Novel Approach to Reduce Local Recurrence

Abstract: BACKGROUND AND AIMS: Endoscopic mucosal resection (EMR) has become the standard for removing large colon polyps but has a 10%-30% recurrence rate using standard techniques. Data shows improved recurrence rates with focal therapy of the edge of the resection base using cautery. We examine a novel technique, hybrid APC assisted EMR, which treats both the edge and the base with cautery to assess its effect on local recurrence. METHODS:We reviewed all EMRs of polyps >2 cm by a single endoscopist with 6-month follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…These reports enrolled 164 subjects, from whom 195 non-pedunculated polyps were removed (166 with hAPC-assisted EMR). Polyps’ size was similar among studies, as was the rate of complete lifting; however, the percentage of en bloc resection varied: 6% in the study by Motchum et al [ 10 ] and 28.8% in that by Levenick et al [ 12 ]. Regarding the hAPC technique, even though the settings were similar (effect 30–50, prior to thermal ablation with 40 watts), both the eschar base and peripheral edges were always ablated only in two of the studies [ 11 , 12 ].…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…These reports enrolled 164 subjects, from whom 195 non-pedunculated polyps were removed (166 with hAPC-assisted EMR). Polyps’ size was similar among studies, as was the rate of complete lifting; however, the percentage of en bloc resection varied: 6% in the study by Motchum et al [ 10 ] and 28.8% in that by Levenick et al [ 12 ]. Regarding the hAPC technique, even though the settings were similar (effect 30–50, prior to thermal ablation with 40 watts), both the eschar base and peripheral edges were always ablated only in two of the studies [ 11 , 12 ].…”
Section: Resultsmentioning
confidence: 76%
“…Three studies [ 10 , 11 , 12 ] evaluated the use of hAPC after EMR of colonic polyps, two of which were prospective [ 10 , 11 ] ( Table 2 ). These reports enrolled 164 subjects, from whom 195 non-pedunculated polyps were removed (166 with hAPC-assisted EMR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the concerns for potential residual microscopic tissue within the EMR resection bed, novel adjuvant techniques such as hAPC applied to the resection bed are undergoing evaluation. Notably, an early pilot study has shown a significant reduction in recurrence, with a 0% recurrence rate at SC1 in patients undergoing adjunctive hAPC versus 20.7% (p=0.01) in the standard EMR arm [5]. However, data from larger comparative studies are needed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Adjuvant techniques such as the application of snare-tip soft coagulation (STSC) to EMR defect edges and hybrid APC (hAPC) have been shown to reduce recurrence from potential non-visible residual microscopic tissue [4,5]. Additionally, new adjunc-Need for adjunctive removal techniques for endoscopic mucosal resection of large non-pedunculated colonic polyps is predictive of recurrence tive techniques such as the use of hot avulsion and cold avulsion with snare-tip soft coagulation (CAST) have been shown to be efficacious in recent years to manage macroscopic polyp tissue not amenable to snare resection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%